(untitled) (Scientific journal of the Fergana State University, 2024)
From the very beginning, the Jadids sought to reform the traditional educational system of Muslim religious schools, new style schools, publishing, and theater, social, political and cultural institutions. This article highlights the study of the educational process and the content of educational activities in the “Bukhara House of Education”.